An experimental investigation of lateral pressure effects on stress relaxation of elastomers. (17th May 2019) - Lu, M; Yun, J; Chen, M H; Sun, L
Abstract: Elastomer creep and stress relaxation are major concerns for sealing applications, especially under high temperature and high pressure (HTHP) environment. Here we report on an experimental study of the lateral pressure effect on compressive response and stress relaxation of elastomers. The experiments were conducted with real time measurements of elastomer stress relaxing under a controlled environmental pressure. Significant lateral effects caused by this additional pressure have been observed in terms of the stress relaxation behavior of hydrogenated nitrile butadiene rubber (HNBR). In comparison to the stress relaxation stress, this small additional pressure brings unexpected significant effects in reducing the elastomer high temperature relaxation characteristics. Better understanding of the influences of such effects can lead to more effective formulation, design and application of elastomer components under complicated HTHP environments.